Discovering Emily Dickinson: After the Critical Turn… Is There Finally a Smile? - Maldonado, Laura (2023)
This paper examines how Emily Dickinson was previously studied and compares it to the most recent critical approaches, particularly on the subject of emotion. Using religious poetry, poetry about nature, and humor, this paper examines the critical interpretations that previously highlighted the role that pain and suffering played in Dickinson’s poetry as well as the gradual change on Dickinson’s critical studies that took place since the seventies. With the growing diversity of critical perspectives, it may come as a surprise that it is still necessary to refer back to the darker image of the poet: why does this image persist? And is it possible to reconcile Dickinson’s popular image with the new critical currents? This article reveals that Dickinson's image is permanently under construction.